2019
DOI: 10.1002/slct.201900857
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel Genistein Amino Acid Ester Derivatives as Potential Anti‐Tumor Agents

Abstract: Thirty‐one novel genistein amino acid ester derivatives were synthesized and evaluated for their anti‐proliferative activities against HUVEC cells and five cancer cells lines (HCT‐116, HeLa, HepG‐2, MCF‐7, MGC‐803). Most of the amino acid ester derivatives exhibited more inhibitory activity than their parent compound genistein. In particular, compound 8 j (methyl(4‐((5‐hydroxy‐3‐(4‐hydroxyphenyl)‐4‐oxo‐4H‐chromen‐7‐yl)oxy)butanoyl)tryptophanate) bearing tryptophan chain showed the most cytotoxicity against HCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Particularly, compound 15 (Figure 5) having the tryptophan chain showed the most potent cytotoxicity against HCT‐116 cells with an IC 50 value of 2.76 μM. Mode of action studies further revealed that compound 15 suppressed the metastasis of HCT‐116 cells and induced the apoptosis in a concentration dependent manner and produces the cell cycle arrest at G1 phase [135] …”
Section: Semi‐synthetic Modification Of Genistein During the Period 2...mentioning
confidence: 98%
See 1 more Smart Citation
“…Particularly, compound 15 (Figure 5) having the tryptophan chain showed the most potent cytotoxicity against HCT‐116 cells with an IC 50 value of 2.76 μM. Mode of action studies further revealed that compound 15 suppressed the metastasis of HCT‐116 cells and induced the apoptosis in a concentration dependent manner and produces the cell cycle arrest at G1 phase [135] …”
Section: Semi‐synthetic Modification Of Genistein During the Period 2...mentioning
confidence: 98%
“…Mode of action studies further revealed that compound 15 suppressed the metastasis of HCT-116 cells and induced the apoptosis in a concentration dependent manner and produces the cell cycle arrest at G1 phase. [135] Bai et al in 2018 reported the antitumor activity of a new synthetic genistein derivative, 5-hydroxy-4'-nitro-7-propionyloxy-genistein (HNPG) 16 (Figure 5) in human ovarian cancer cells A2780. The compound has shown to inhibit the proliferation, invasion and metastasis and induced the apoptosis in a dose and time dependent manner.…”
Section: Human Breast Cancer Cells (Mcf-7)mentioning
confidence: 99%
“…Amino acid has played an important role in therapeutics from the earliest days of modern drug discovery . Recently, nonproteinogenic α-amino acids are found as substructures in various pharmaceuticals, such as antibiotic, antiparkinsonian, and antitumor drugs (Scheme ). As a result, there have been extensive studies on the synthesis of amino acids, especially the construction of amino acid skeleton since it avoids restriction from the derivatization of naturally occurring compounds .…”
mentioning
confidence: 99%
“…99 mg (60%): colorless oil. 1 H NMR (400 MHz, CDCl 3 ) δ 8.43 (ddd, J = 4.9, 2.0, 0.8 Hz,1H),7.58 (ddd,J = 8.2,7.4,2.0 Hz,1H),2H),3H),1H),7.04 (ddd,J = 7.3,4.9, 1.0 Hz, 1H), 5.78 (q, J = 7.1 Hz, 1H), 1.70 (d,J = 7.1 Hz,3H), 1.27 (s, 9H). 13 C{ 1 H} NMR (100 MHz, CDCl 3 ) δ 154.…”
mentioning
confidence: 99%